EXPLORING HYPERGLYCEMIA-RELATED SEIZURES: A CASE SERIES - Hannah, Chen; Sim, Sing Yee; Chan, Pei Lin; Florence Tan, Hui Sieng (2025)
Introduction/Background Hyperglycemia-related seizures, though rare, represent a serious complication of uncontrolled diabetes, often occurring in the context of Hyperosmolar Hyperglycaemic State (HHS). We present a retrospective case series detailing the clinical characteristics, metabolic parameters and outcomes of patients admitted with hyperglycemia-related seizures.